PERTUMBUHAN KEDELAI (Glycine max L. Merrill) DENGAN APLIKASI FUNGI MIKORIZA ARBUSKULAR (FMA) DAN KONSORSIUM MIKROBA - Dini Oktaviani; Yaya Hasanah; Asil Barus (Jurnal Agroekoteknologi, 2014)
The using of chemical fertilizer in soybean cultivation had created negative impact for environment.To decrease of it, the utilization of biological fertilizer in soybean cultivation can increase thegrowth and production of soybean. The objective of the research was to know the growth andproduction of soybean with application of Arbuscular Mycorrhizal Fungi (AMF) and microbeconcortium. This research was conducted at Jalan Setiabudi Kelurahan Simpang SelayangKecamatan Medan Tuntungan on April-July 2013, used factorial randomized block design with twofactors. The first factor was application of AMF (0, 20, 40 g per plant). The second factor wasapplication of microbe concortium (0,5,10,15 g per kg of seed). Parameters observed were plantheight, stem diameter, infection degree of AMF, weight of nodules and number of effectivenodules. The result showed that application of AMF increased plant height 6 weeks after plant(WAP), stem diameter, infection degree of AMF. The application of microbe concortium increasedplant height 6 WAP, stem diameter, infection degree of AMF. Interaction both of treatmentincreased plant height 2 WAP, weight of nodules and number of effective nodules.Keywords : soybean, arbuscular mycorrhizal fungi, microbe concortium